2010
DOI: 10.1093/chemse/bjq079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stimulation of the Laryngopharynx with Water and Salt Solutions on Voluntary Swallowing in Humans: Characteristics of Water Receptors in the Laryngopharyngeal Mucosa

Abstract: Stimulation of water receptors in the laryngopharynx (LP) with water facilitates voluntary swallowing in humans. Based on measures of swallowing intervals (SIs) in repetitive swallowing, we investigated characteristics of laryngopharyngeal water receptors in humans. Healthy adult volunteers were instructed to perform repetitive swallowing as quickly as possible during infusion of a solution into the LP. Infusion of water shortened SI, suggesting that water excites water receptors. Infusion of 0.3 M NaCl soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Such facilitatory effect of water stimulation to the pharyngeal region on swallow initiation has also been reported by others, showing that application of water to the laryngopharynx shortened swallowing intervals in repetitive voluntary swallowing in humans [13,14]. They also showed that application of 0.3 M NaCl solution prolonged swallowing intervals, and suggested that the action of NaCl is inhibition of water response [14]. The present result showing the suppression of swallow initiation by application of saline (0.15 M NaCl) may partly support their idea.…”
Section: Effect Of Application Of Solutions To the Oropharynxsupporting
confidence: 74%
See 1 more Smart Citation
“…Such facilitatory effect of water stimulation to the pharyngeal region on swallow initiation has also been reported by others, showing that application of water to the laryngopharynx shortened swallowing intervals in repetitive voluntary swallowing in humans [13,14]. They also showed that application of 0.3 M NaCl solution prolonged swallowing intervals, and suggested that the action of NaCl is inhibition of water response [14]. The present result showing the suppression of swallow initiation by application of saline (0.15 M NaCl) may partly support their idea.…”
Section: Effect Of Application Of Solutions To the Oropharynxsupporting
confidence: 74%
“…The finding strongly suggests that umami stimulation of the oropharynx facilitates the initiation of the swallow reflex. However, we cannot deny the possibility that the effect of umami solution was due to the vehicle (water), which is already known to be a major chemical stimulant of this area and an initiator of the swallow reflex [13,14]. To clarify this, we examined whether application of MSG solution dissolved with saline as well as distilled water to the oropharynx modulates the initiation of the swallow reflex.…”
Section: Introductionmentioning
confidence: 99%
“…The swallowing reflex evoked by water is believed to depend on the activation of water receptors [34], whereas acid stimulation may depend on transient receptor potential vanilloid type 1 (TRPV1) channels expressed in laryngopharyngeal afferent nerve fibers [35]. Activation of TRPV1 by acidity, heat, or capsaicin is known to induce SP release from laryngopharyngeal afferent nerve endings, triggering the swallowing and cough reflex [36].…”
Section: Discussionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 4 The potentials required to initiate voluntary swallowing have been found to vary greatly from subject to subject, even in healthy humans [10][11][12]. Human brain imaging has exposed the cortical representation of voluntary swallowing [13][14][15][16][17][18].…”
Section: Accepted Manuscriptmentioning
confidence: 99%